Single-Atom Engineering to Ignite 2D Transition Metal Dichalcogenide Based Catalysis: Fundamentals, Progress, and Beyond - Wang, Xin; Zhang, Yuwei; Wu, Jing; Zhang, Zheng; Liao, Qingliang; Kang, Zhuo; Zhang, Yue (Chemical reviews, 2022)
Single-atom catalysis has been recognized as a pivotal milestone in the development history of heterogeneous catalysis by virtue of its superior catalytic performance, ultrahigh atomic utilization, and well-defined structure. Beyond single-atom protrusions, two more motifs of single-atom substitutions and single-atom vacancies along with synergistic single-atom motif assemblies have been progressively developed to enrich the single-atom family. On the other hand, besides traditional carbon material based substrates, a wide variety of 2D transitional metal dichalcogenides (TMDs) have been emerging as a promising platform for single-atom catalysis owing to their diverse elemental compositions, variable crystal structures, flexible electronic structures, and intrinsic activities toward many catalytic reactions. Such substantial expansion of both single-atom motifs and substrates provides an enriched toolbox to further optimize the geometric and electronic structures for pushing the performance limit. Concomitantly, higher requirements have been put forward for synthetic and characterization techniques with related technical bottlenecks being continuously conquered. Furthermore, this burgeoning single-atom catalyst (SAC) system has triggered serial scientific issues about their changeable single atom–2D substrate interaction, ambiguous synergistic effects of various atomic assemblies, as well as dynamic structure–performance correlations, all of which necessitate further clarification and comprehensive summary. In this context, this Review aims to summarize and critically discuss the single-atom engineering development in the whole field of 2D TMD based catalysis covering their evolution history, synthetic methodologies, characterization techniques, catalytic applications, and dynamic structure–performance correlations. In situ characterization techniques are highlighted regarding their critical roles in real-time detection of SAC reconstruction and reaction pathway evolution, thus shedding light on lifetime dynamic structure–performance correlations which lay a solid theoretical foundation for the whole catalytic field, especially for SACs.